1998
DOI: 10.1007/s004410051037
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of annexin 5, a calcium-dependent phospholipid-binding protein, in rat endocrine organs

Abstract: Annexin 5, a unique calcium- and phospholipid-binding protein, has been investigated for its specific distribution in rat endocrine organs by immunocytochemistry with a specific antiserum to recombinant rat annexin 5. Follicular epithelial cells and parafollicular cells of the thyroid gland, adrenocortical cells of the zona fasciculata and zona reticularis, luteal cells, testicular interstitial cells, and Sertoli cells were shown to contain annexin 5. To examine whether the synthesis of annexin 5 would be affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 17 publications
3
26
1
Order By: Relevance
“…However, it is not known whether the phospholipid binding is physiologically relevant to some particular function. Our findings here, together with our previous results [6][7][8]52], suggest a role for annexin A5 in signal transduction in the gonadotropes. This idea is further supported by the results reported by other groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, it is not known whether the phospholipid binding is physiologically relevant to some particular function. Our findings here, together with our previous results [6][7][8]52], suggest a role for annexin A5 in signal transduction in the gonadotropes. This idea is further supported by the results reported by other groups.…”
Section: Discussionsupporting
confidence: 87%
“…Annexin V could also be involved in the lower insulin secretion. It is a member of a calcium-dependent phospholipid-binding protein family, which participates in vesicular transport specifically in plasma membrane to membrane or plasma membrane to cytoskeleton interactions [74]. Likewise, nucleobindin 2 is a DNA-and calcium-binding protein, which is involved in establishing the agonistmobilisable Golgi Ca 2+ store, together with the sarcoplasmic and endoplasmic reticulum calcium ATPase (SERCA) and the inositol triphosphate 3 receptor (IP3R) [101].…”
Section: Discussionmentioning
confidence: 99%
“…We found that annexin 5 distributes also in lactotropes and other pituitary cells [11,14], although the intensity is less than that of the gonadotropes and it has yet to be determined whether annexin 5 is synthesized in these cell species or not. Annexin 5 was shown to inhibit prolactin release, even though the degree of inhibition was not very high in primary pituitary cell cultures [14].…”
mentioning
confidence: 81%
“…Although the biochemical properties of annexinfamily proteins suggest roles in significant cell functions, the function of these proteins in physiological processes is still obscure [7]. We previously demonstrated that annexin 5 is synthesized in the anterior pituitary gland [8] and later found that it is produced by pituitary gonadotropes under the regulation of gonadotropin releasing hormone (GnRH) [9][10][11][12][13]. As annexin 5 augments gonadotropin secretion in vitro [13] and antisense oligodeoxynucleotide to annexin 5 mRNA retards luteinizing hormone release by GnRH, annexin 5 is thought to mediate at least part of the action of GnRH on pituitary gonadotropes [13].…”
mentioning
confidence: 99%